Effect of Genotype and Explant Type on Shoot Regeneration in Tomato (Lycopersicon esculentum Mill.) in vitro - J. Gubiš; Z. Lajchová; J. Faragó; Z. Jureková (Czech Journal of Genetics and Plant Breeding, 2003)
The regeneration capacity of six types of explants (segments from hypocotyl, cotyledons, epicotyl, leaf, internodes and petiole) was compared in 13 cultivars of tomato (Lycopersicon esculentum Mill). Explants were cultured on a regeneration medium containing 1 mg/l zeatin and 0.1 mg/l indole-3-acetic acid. The number of shoot primordia and shoots with 1 or more fully developed leaves was evaluated after 6 weeks. The regeneration capacity was significantly influenced by cultivars and explant types. The total number of shoot primordia produced in all types of explants was highest in the cultivars Hana and Premium and lowest in UC 82 and Money Marker. Cv. Hana also produced the highest number of shoots. The most responsive explants in most cultivars were hypocotyls and epicotyls with up to 100% regeneration and mean production of 6.3 and 6.5 shoot primordia per explant, respectively.